The Performance of Existing Rice Farming on Peatlands in Central Kalimantan Food Estate Area - Mulyono, Joko; Syahyuti, Syahyuti; Gunawan, Endro (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 17 No 3 (2023): Vol 17 No 3 (2023), 2024)
Peatland is tidal wetland that has the potential to be utilized for rice farming. This study aims to identify the characteristics of farmers and rice farming performance, and analyze the feasibility of rice farming on peatlands in the Food Estate area, Central Kalimantan. The research was conducted in Kapuas and Pulang Pisau districts, Central Kalimantan, in 2020. Primary data were obtained through interviews with 180 farmers purposively selected as research respondents. Farmers’ characteristics and rice farming performance were analyzed using descriprive qualitative and quantitative approaches. The feasibility of rice farming was analyzed using RC ratio. The results showed that in general, the farmers were productive with a long experience of rice farming despite low education. Land ownership is quite extensive with self-owned status. Farmers in Kapuas district used hybrid and labeled rice seeds (85.87%), while in Pulang Pisau district the seeds used were inbred and only 42.86% were labeled. The farmers also used inorganic fertilizer, organic fertilizer, lime, herbicides and pesticides. Rice farming on peatlands in the Food Estate area of Central Kalimantan is feasible with RC > 1. Rice farming on peatlands should be widely developed to support the increase in national rice production, in line with the increasing demand for rice